SKRINING KANKER SERVIKS DENGAN PEMERIKSAAN PAP SMEAR PADA PROFESI BIDAN DI RUMAH SAKIT TK II PUTRI HIJAU MEDAN TAHUN 2017 - Syaiful, Syaiful; Tarigan, Frida Lina; Zuska, Fikarwin (Jurnal Riset Hesti Medan, 2018)
Cervical cancer is a malignant tumor that grows inside the cervix (the lowest part of the uterus attached to the top of the vagina). A Pap smear is a method in which a cell is taken from the cervix and examined under a microscope. Any woman who is 18 years old, or a woman who has been sexually active should begin a Pap smear. This check should be done every year, although there are no symptoms of cancer. An examination of more than a year if it reaches the age of 65 years or three previous consecutive checks shows normal results. The purpose of the study changed the behavior of the midwife profession in order to perform cervical cancer screening with pap smear examination at Tk II Putri Hijau Hospital Medan. The design of this research is qualitative through phenomenology approach. The result of the research was obtained by the informant as many as 8 people consisting of 1 male informant that is obgyn doctor, 7 person work as midwife consisting of informant 2 often doing pap smear examination. Informants who do not routinely perform pap smear examination of informants 3 informants 3 times, informant 4 as much as 1 times, informant 5 as much as 3 times, informant 6 as much as 2 times. While informant 7 has never done pap smear examination, and informant 8 as much as 1 times. Some of the reasons that changed the behavior of the midwife profession to the Pap smear examination were shyness (fear), fear, no complaints (abnormalities), kesetrilan (medical equipment), lazy and cost. Here is found the expression of the eight informants is a more dominant shame words. Suggestion for the Tk II Putri Hijau Medan, submitted to the leader to oblige all female sex workers who have been actively engaged in sexual intercourse to perform cervical cancer screening by Pap smear examination routinely according to procedure and done at Tk II Putri Hijau Hospital Medan for free with existing health insurance facilities.Keyword: Cervical cancer screening, Pap smear Examination, Midwife Profession.